Children around the world : the future of our earth - Rygaard, Niels Peter; Gielen, Uwe P. 1940-; Congress, Elaine Piller; Larock, Julia (International psychology (Charlotte, N.C.), 2024)
"The fourth book in the UN book series Behavioral Science in the Global Arena is entitled Children Around the World: The Future of Our Globe continues the focus on issues of major international importance. This book is based on these three principles 1. Focus on most important pressing issues, 2, is multidiscipline with authors who are psychologists, social workers, medical doctors, and NGO leaders. And 3. Most chapters are co-authored by well-known experts and new professionals or graduate students. Children were chosen as the focus as over 30% of the people in our world are children. This book looks at major macro trends affecting children as well as interventions that have been used to address problems that children face. Topics that are addressed include the UN Convention on Children, Non-Governmental Organizations (NGOs) that support children, and development issues like pre and post-natal health, family systems, gender roles, and puberty/adolescent issues. Attention is given to major risk factors and challenges such as sex trafficking, child labor, street children, protecting children in congregate care, and violence against children in the home, in institutions, and in the community. This book closes with a look at the most serious future challenges for children including literacy, migration, and mental health issues. This book is designed for faculty and students, as well as professionals who want to learn more about the type and severity of problems affecting children as well as positive interventions that have been used to address these problems"--